Interplay between bile acids, gut microbiota, and the tumor immune microenvironment: mechanistic insights and therapeutic strategies - Tong, Yan; Lou, Xiaojun (Frontiers in Immunology, 2025)
The interplay between the gut microbiota, bile acid (BA) metabolism, and the tumor immune microenvironment (TIME) is a critical and rapidly advancing field in cancer immunology. Microbiota-transformed bile acids act as pivotal signaling molecules. This review systematically dissects how these BAs engage host receptors (e.g., FXR, TGR5, VDR, S1PR2) to influence the differentiation and activity of key innate (macrophages, NK cells, MDSCs, DCs) and adaptive (CD8+ T cells, Tregs, Th1/Th17 cells) immune cell populations within the TIME. We underscore that dysregulation of this microbiota-BA-immune axis, prevalent in gastrointestinal and hepatobiliary cancers, frequently cultivates a pro-inflammatory, immunosuppressive TIME, thereby facilitating tumor immune evasion and progression. In light of this, we examine emerging therapeutic strategies aimed at reprogramming this axis, including pharmacological BA receptor modulation, microbiota-based interventions (e.g., engineered microbes, FMT, dietary strategies), and their synergistic potential with established cancer treatments like immune checkpoint inhibitors. Finally, this review addresses significant challenges in clinical translation, including inherent axis complexity, inter-individual variability, and methodological hurdles. Future directions highlighted include tackling heterogeneity, employing advanced multi-omics, and developing robust biomarkers for precision immuno-oncology. Unraveling this complex immunometabolic network is crucial for identifying novel diagnostic tools and advancing next-generation cancer immunotherapies.